Implementasi Kebijakan Keterbukaan Informasi Publik di Jawa Timur Tahun 2016 - Zulaikha, Zulaikha; Paribrata, Agni Istighfar (Faculty of Communications Science, Dr. Soetomo University, 2017)
The public information disclosure policy has entered its 7th year of implementation since it was enacted in 2008 and began to be implemented in 2010. As with other procedures, monitoring and evaluation are required in the application so that the policy implementation does not deviate from the expected. In this Jokowi administration era, the ideas to realise open government are getting closer to the support of the development of information technology. But how is it implemented in the area? This research wants to photograph the implementation of public information disclosure policy in East Java, consisting of 38 districts/municipalities and 56 units of regional apparatus. The results of this study indicate that for the district or city government, the implementation of this information disclosure policy has been an encouraging development, but not so with the Regional Device Work Unit. Likewise, the Information Management and Documentation Officer also experienced progress although there are still shortcomings in the implementation of its duties.